Assessment of the development of foreign trade in high-tech production of Ukraine under the association with the EU - Matyushenko, Igor; Hlibko, Serhii; Petrova, Mariana Mateeva; Pasmor, Maryna Serhiivna; Loktionova, Maryna (Business, Management and Economics Engineering, 2020)
Purpose – the purpose of article should assess the main factors affecting the development of trade in high-tech products of Ukraine in the context of association with the EU and the spread of a new industrial revolution.Research methodology – the scheme of research of trade of high-tech products of Ukraine from the EU on the basis of qualitative and quantitative economic-statistical analysis, analysis of comparative advantages and correlation-regression analysis.Findings – the results of the analysis show that the main factors determining the low presence of Ukraine in the world market of high-tech products are the outdated structure of production, a low level of R&D costs, and a decrease in the innovative activity of Ukrainian enterprises. The article presents the author’s recommendations on improving the effectiveness of foreign trade in high-tech products of Ukraine in the EU market.Research limitations – the absence of a state development strategy for the production of hightech products does not make it possible to accurately determine indicators of scientific research of the potential of Ukraine.Practical implications – correlation-regression analysis results can be used in the private and state sectors of the economy of Ukraine.Originality/Value – the original combination of schemes and methods allowed us to identify new critical places for export development in the context of the association of Ukraine with the EU.